To appoint their "moor women": female characters made of otherness in Spanish literature of the twentieth century (Ogigia. Revista Electrónica de Estudios Hispánicos, 2018)
This paper reflects on the different designations that Moroccan female characters receive in twentieth-century Spanish literature written by women. These female characters are said that they are Moors, Arabs, Muslims, Berbers, Indigenous, Riffian, Saracens, Bedouins, Mohammedans or, simply, Moroccans. A wide range of terms that point to ethnolinguistic, religious or origin categories, totally different and that, therefore, designate different human types. However, in this analyzed narrative they are used almost indistinctly and, for it, we seek to reflect for what reason.
Keywords: Spanish literature; Moor women; Women writers; Otherness; Morocco